Pendampingan Penyusunan Profil Kampung Ifar Besar Tahun 2024: Assistance in the Preparation of the Ifar Besar Village Profile in 2024 - Iriyanto, Santje Magdalena; Zulfiana T, Indah Sari; Musfira, Musfira; Salipu, M. Amir; Usman, Syamsudin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
A village profile is a comprehensive description of the village's character, in the form of basic data: natural resources, human resources, institutions, facilities, and infrastructure as well as village developments and problems. Until early 2024, this Community Service (PKM) is aimed at assisting in preparing village profiles by updating data and information on the character of Ifar Besar village. The method chosen is assistance in updating data based on basic data about natural resources, human resources, institutions, facilities, and infrastructure as well as institutions. PKM assistance in preparing the profile of Ifar Besar village is; first, compiling data on village potential and problems; second, updating data on village potential and problems to determine village development policies according to future needs. The results of assistance with the profile of the Ifar Besar village, in the form of a village profile compilation completed with thematic maps, tables, and diagrams, has been a success as indicated by an increase in the knowledge of village officials in updating data assisted by students who are doing Community Service Program. Based on the results of interviews with 20 participants, 17 participants (85%) stated that their understanding and skills had increased regarding collecting and processing village data. Furthermore, 18 participants (90%) considered that the resulting village profile was very useful for planning sustainable development in the future. Indirectly, this success also shows that the obstacles faced by Ifar Besar Village are not only human resources but also financial support as well as facilities and infrastructure.